Use of computer in drug design and drug discovery: A review (International Journal of Pharmaceutical and Life Sciences, 2012)
Drug design through computer, a recent, very effective technique in modern arena. Now a days Computer Aided Drug Design (CADD) technologies are used in nanotechnology, molecular biology, biochemistry etc. The main benefit of the CADD is cost effective in research and development of drugs. There are wide ranges of software are used in CADD, Grid computing, window based general PBPK/PD modeling software, PKUDDS for structure based drug design,APIS, JAVA, Perl and Python, CADD as well as software including software libraries. There are different techniques used in CADD visualization, homology, molecular dynamic, energy minimization molecular docking, QSAR etc. Computer aided drug design is applicable in Cancer disease, transportation of drug to specific site in body, data collections and storages of organics and biologicals. Conformational properties and energetics of small molecules and DNA cleavage, molecular diagnostics based on fluorescences are focusing using this technique. DOI: http://dx.doi.org/10.3329/ijpls.v1i2.12955 International Journal of Pharmaceutical and Life Sciences Vol.1(2) 2012